2019
DOI: 10.1093/condor/duz032
|View full text |Cite
|
Sign up to set email alerts
|

Global positioning system tracking devices can decrease Greater Sage-Grouse survival

Abstract: Reliable demographic estimates hinge on the assumption that marking animals does not alter their behavior, reproduction, or survival. Violations can bias inference and are especially egregious for species of high conservation concern. Global positioning system (GPS) devices represent a recent technological advancement that has contributed greatly to avian ecological studies compared with traditionally used very high frequency (VHF) radio transmitters, but may affect demographic rates differently than VHF trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 55 publications
6
41
5
Order By: Relevance
“…Thus, we suggest researchers and managers currently deploying this design, recapture fitted birds and report findings. The negative effects we observed from rump‐mount transmitter design and attachment could be especially pronounced in small populations of greater sage‐grouse or threatened Gunnison sage‐grouse (Barron et al 2010, Ouren et al 2018, Severson et al 2019). Our modified harness design and detailed protocols will help alleviate potential injuries especially to male greater sage‐grouse, and we encourage developing protocols to mitigate these potential effects.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, we suggest researchers and managers currently deploying this design, recapture fitted birds and report findings. The negative effects we observed from rump‐mount transmitter design and attachment could be especially pronounced in small populations of greater sage‐grouse or threatened Gunnison sage‐grouse (Barron et al 2010, Ouren et al 2018, Severson et al 2019). Our modified harness design and detailed protocols will help alleviate potential injuries especially to male greater sage‐grouse, and we encourage developing protocols to mitigate these potential effects.…”
Section: Discussionmentioning
confidence: 95%
“…Rappole and Tipton (1991) also cautioned against using leg-loop harness materials that are (or become) too narrow and result in irritation. If the mark influences behavior or survival, it could result in misleading inferences related to demographic rates, habitat use, and movement (Foster et al 2018, Severson et al 2019. We suggest additional research into this topic and recommend that investigators planning to use a rump-mount harness on male or female greater sage-grouse consider adopting our harness design or develop a new or improved design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trackers were built at the maximum weight capacity for pheasants to maximize data accruement. However, concerns regarding the influence of GPS receiver weight on survival and behavior may limit application for smaller species (Foster et al 2018, Severson et al 2019. Therefore, researchers should be weary of weight thresholds for specific species.…”
Section: Discussionmentioning
confidence: 99%
“…obs.). Some studies have shown that carrying of GPS-tags can increase predation risk for birds by making them more visible and reducing their ability to escape predators (Severson et al 2019). However, it is unclear whether this happened to juveniles of the WBW.…”
Section: Discussionmentioning
confidence: 99%